Intravoxel incoherent motion magnetic resonance imaging findings in the acute phase of MELAS: a case report - Uehara, Ryuji (BlackWell Publishing Ltd, 2014)
OBJECTIVE: We report the clinical application of intravoxel incoherent motion (IVIM) magnetic resonance (MR) imaging to diagnose a case of mitochondrial myopathy, encephalopathy, lactic acidosis, and stroke-like episodes (MELAS) in the acute phase. RESULTS: On IVIM MR Images of this patient, higher perfusion (f) and diffusion (D) values in the left occipital and temporal lobes were found compared to the contralateral areas. CONCLUSION: These findings imply a breakdown of autoregulation with hyperperfusion and vasogenic edema during the acute phase of MELAS, as described in previous reports. IVIM imaging is a valuable, noninvasive tool that simultaneously quantifies perfusion and diffusion parameters.